PROFIT-SHARING IN CATTLE COORPORATION PROJECT: An analysis of the Mudharabah Contract Model in Islamic Law - Setia, Setia; Kamal, Marium (JURISTA: Jurnal Hukum dan Keadilan, 2023)
This research aims to find out how the practice of profit-sharing cooperation takes place and the forms of default that occur between cattle owners and managers in Cot Cut Village, Aceh-Indonesia. The research uses qualitative methods (field research) through interview and observation techniques, as well as secondary data obtained through library research by examining books, journals, propositions and literature related to the research. The results of the research show that cooperation is carried out through verbal agreements without time limits and profit-sharing methods based on the sex of the cow and also the profit sharing for calves. Uncertainty regarding profit sharing occurs when the cows being sold are sick or the profit sharing is slaughtered which causes uncertainty in the profit sharing. The form of the agreement is in accordance with contract law such as Article 1320 of the Civil Code, however, verbal agreements are weak in terms of proof when there is a breach of contract, and based on Islamic agreements, cooperation in raising cattle is in accordance with fulfilling the pillars and conditions of Islamic agreements, especially Mudharabah contracts, but in terms of this contract If a default occurs, such as the imposition of compensation (dhaman) and a cut in the ratio, it can result in damaging the validity of the contract due to the lack of clarity and loss of profits received by the manager